2017
DOI: 10.5335/rtee.v23i48.7368
|View full text |Cite
|
Sign up to set email alerts
|

Mensuração de perdas de pós-colheita na cadeia de suprimento de moageiras do trigo no Rio Grande do Sul

Abstract: ResumoEste artigo tem como principal objetivo mensurar as perdas físicas e econômicas observadas na cadeia de suprimentos das moageiras de trigo do Rio Grande do Sul (RS). A partir da aplicação de questionário com representativos agentes do setor, a cadeia logística do trigo no RS foi caracterizada e as perdas do produto em cada etapa da cadeia foram quantificadas. Para os fluxos de transporte característicos de mercado interno, as perdas representam 11,41% da quantidade total de trigo em grão oriundos das faz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…As an example, the consumption and distribution phase varies between 10% and 30% of the total of meals produced and not consumed, and are similar to each other (Leinig et al, 2017, Gonzáles et al, 2017, Galian et al, 2016, Pistorello et al, 2015, Parisoto et al, 2013, Pikelaizen e Spinelli, 2013, Fugii et al, 2010, Ricarte et al, 2008. In the post-harvest, processing, and transportation phases, the products still differ according to their food group, chain size, type of processing and logistics (Rocha et al, 2017, Ribeiro et al, 2014, Foscaches et al, 2012, Costa et al, 2011, Costa e Caixeta Filho, 1996 Another point to be observed is that losses in production were not evaluated, probably because of the difficulty in determining it, because it is an expensive process that requires time and labor for its execution. The most commonly found in the literature are those referring to using new technologies, mainly in pest control.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the consumption and distribution phase varies between 10% and 30% of the total of meals produced and not consumed, and are similar to each other (Leinig et al, 2017, Gonzáles et al, 2017, Galian et al, 2016, Pistorello et al, 2015, Parisoto et al, 2013, Pikelaizen e Spinelli, 2013, Fugii et al, 2010, Ricarte et al, 2008. In the post-harvest, processing, and transportation phases, the products still differ according to their food group, chain size, type of processing and logistics (Rocha et al, 2017, Ribeiro et al, 2014, Foscaches et al, 2012, Costa et al, 2011, Costa e Caixeta Filho, 1996 Another point to be observed is that losses in production were not evaluated, probably because of the difficulty in determining it, because it is an expensive process that requires time and labor for its execution. The most commonly found in the literature are those referring to using new technologies, mainly in pest control.…”
Section: Resultsmentioning
confidence: 99%